Effect of Kerosene and Gasoline on Some Properties of High Performance Concrete (Journal of Engineering, 2011)
During the last quarter century, many changes have taken place in the tanks industry and also in the materials that used in its production، while concrete is the most suitable material where concrete tanks has the benefits of strength, long service life and cost effectiveness. So, it is necessary improvement theconventional concrete in order to adapt the severe environment requirements and as a result highperformance concrete (HPC) was used. It is not fundamentally different from the concrete used in the past, although it usually contains fly ash, ground granulated blast furnace slag and silica fume, as well assuperplasticizer. So, the content of cementitious material is high and the water/cement ratio is low. In thisstudy, the silica fume and superplasticizer were used for obtaining HPC. This paper is an attempt to provide some information about effect kerosene and gasoline on some properties of HPC which can be used as storage tanks for petroleum products. The experimental work in this research including; slump test, weight loss test and compressive strength test were performed. The results of these investigations indicated that the petroleum products have unacceptable effects on the properties of concrete.